The research of the kinetics of sunflower cake extraction by ethyl alcohol - Петік, Павло Федорович; Гірман, Валерій Васильович; Мазур, Олена Валеріївна (Eastern-European Journal of Enterprise Technologies, 2014)
The present paper deals with theoretical and experimental substantiation of the basic process laws of the sunflower cake extraction by unconventional solvent - ethyl alcohol. Industrial samples of sunflower cake in the form of granules and grits, for which the porosity parameters (porosity and filtration ratios) were defined, were subjected to the test. Physical model of the 8-step extractor, operating by the countercurrent irrigation principle was developed using a specially designed laboratory setup. The influence of some technological factors (duty of water, extraction time and oilseed material structure) on the sunflower oil extraction kinetics (original cake oil content variation in time) and miscella concentration at each extraction stage was experimentally found. Based on the experimental results, internal diffusion coefficient for ethanolic extraction of sunflower cake, depending on the porosity and filtration indicators was calculated using MathCad and MicrosoftExsel application package. It was shown that improved ethyl alcohol percolation in the granule is confirmed by the higher value of the coefficient of internal diffusion in the granule. The latter is about 2 times higher than that for the hexane extraction. New scientific data for the formulation of the values of process parameters for future technology were obtained.